Chińsko-hinduska współpraca gospodarcza na przełomie XX i XXI wieku - Sporek, Tadeusz (The Chinese-Indian economic co-operation at the turn of the XX and XXI century, 2009)
The turn of the XX and XXI century sees the growing importance in the world economy of the two most rapidly developing and most important after Japan economies, which are China and India. In 2007, the trade volume of these countries reached the level of USD 39 billion. The co-operation of these countries in the ASEAN group involves the following sectors: energy, transport, health protection, culture, tourism, and scientific research, inclusive of IT & teleinformatic technology
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 340-348